2015
DOI: 10.1007/s12031-015-0574-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of miR-132, miR-146a, and miR-155 on MRP8/TLR4-Induced Astrocyte-Related Inflammation

Abstract: Astrocyte activation, associated with the release of pro-inflammatory cytokines interleukin 1-β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α), is a hallmark of multiple brain diseases, including mesial temporal lobe epilepsy. In recent years, several microRNAs have emerged as important controllers of Toll-like receptor (TLR) signaling. In this study, we investigated the effect of miR-132, miR-146a, and miR-155 on myeloid-related protein-8 (MRP8) induced astrocyte-related inflammation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 65 publications
0
45
1
1
Order By: Relevance
“…MicroRNA-132 (miR-132) is significantly upregulated during active synaptogenesis and plays important roles in spine formation and maturation [25]. miR-132 also regulates the inflammatory response and neuronal apoptosis after acute brain injury [6–8]. Several studies have shown that miR-132 is persistently upregulated during epileptogenesis after acute brain injury [913].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA-132 (miR-132) is significantly upregulated during active synaptogenesis and plays important roles in spine formation and maturation [25]. miR-132 also regulates the inflammatory response and neuronal apoptosis after acute brain injury [6–8]. Several studies have shown that miR-132 is persistently upregulated during epileptogenesis after acute brain injury [913].…”
Section: Introductionmentioning
confidence: 99%
“…We showed in Fig A in S1 File that HSVE in our mouse model was associated with astrocytosis and the role of astrocytes in infectious disease in the brain is a relatively unexplored avenue for further research. MiR-146a and miR-155 have both been shown to play roles in astrocyte-mediated neuroinflammation [64]. In addition miR-141 is expressed in normal human astrocytes and the role for this miRNA in these cells, and other members of miR-200 family and miR-182 cluster, has not yet been investigated [65].…”
Section: Discussionmentioning
confidence: 99%
“…miR-212-3p and miR-132-3p work synergistically to control Sox11 expression in the setting of epilepsy [22]. miR-132 play a negative feedback regulator of IL-1β and IL-6 by targeting IRAK4 in astrocyte-related inflammation induced by MRP8 [23] and promotes epileptogenesis by modulating BDNF/TrkB and p250GAP/Cdc42 signaling in the hippocampal neuronal culture model [24, 25]. Figure 3B…”
Section: Resultsmentioning
confidence: 99%
“…What is important is IRAK4, a genes associated with epilepsy [23], presented correlation with both miRs and whose dysregulation significantly related to poor survival in several human cancer. Apart from the somatic mutations of IRAK4 itself, all indicated miRs may target single gene to interfere the process of cancer and epilepsy.…”
Section: Discussionmentioning
confidence: 99%